Avaliação da perda de solo por fluxo superficial utilizando parcelas experimentais: estudo de caso na bacia hidrográfica do Córrego do Glória em Uberlândia MG - Silva, Josenilson Bernardo da (2006)
The action human being in the natural environment comes generating one serie of ambient problems. The withdrawal of the natural covering for increase of the destined areas agriculture increases to each year. The deforestation is the initial point to unchain a gamma of ambient problems. It is distinguished those that are, also, influenced for the rain. The overland flow has the power, throughout its way covered in the surface, to disaggregate and to carry essential elements to the ground. Moreover, the natural characteristics of soil go separately or in set, to facilitate the sprouting of this draining on the surface. The plots had been decisive instruments in this inquiry, therefore, the data collected in field had served substantially for the interpretations contained in this work. The granulometry test is important to have in mind its texture, but, the necessity of elaborated tests exists more and to go to the field with bigger regularity, is excellent. To its end, one perceived that the necessity to study related subjects the soilloss and rainfall requires more time so that if it can implement finer tests and to help more in the search of based elements on the erosive process influenced by the overlandflow.